BANK DAN ASURANSI: PERAN KINERJA ASET PERBANKAN DALAM PENINGKATAN KINERJA ASURANSI - Yulianto, Krist Setyo; Hariwibowo, Ignatius Novianto (Program Studi Akuntansi, Universitas Kuningan, 2024)
Abstract Banking industry transactions with the insurance industry have strong ties, in an effort to manage financial risk. Therefore, this study was conducted to provide an overview of the role of banking industry credit performance in improving the performance of the insurance industry. This research uses correlation and regression tests in the context of a description approach. The data used is banking and insurance performance data published on the Otoritas Jasa Keuangan website in 2022. This study assesses the correlation of non-perform asset (NPA) ratios in improving insurance performance assessed from four claim adequacy ratios, insurance session ratios, and investment to technical reserve ratios, in three insurance industry groups. The results of this study indicate that the NPA ratio has a weak correlation to the claim adequacy ratio, has a moderate to strong correlation for the insurance session ratio and investment to technical reserves. However, the results of this study show a very strong negative correlation between the NPA ratio and the insurance session ratio in the general insurance industry group. Thus, NPAs have an influence on the insurance session ratio. Keywords: insurance performance, non-performing assets, credit performance, financial risk